Effect of coal thicknesses on energy evolution characteristics of roof rock-coal-floor rock sandwich composite structure and its damage constitutive model. (1st October 2020) - Ma, Qing; Tan, Yunliang; Liu, Xuesheng; Gu, Qingheng; Li, Xuebin
Abstract: The stability of the sandwich composite structures formed by leaving coal pillar, roof rock and floor rock (RCF) is of great significance to safe production of coal mines. The failure of coal and rock is actually a state instability phenomenon driven by energy. In order to explore energy characteristics of RCF sandwich composite structures, uniaxial compression tests with different coal thicknesses were performed by numerical simulation tests. The test results show that the strength and elastic modulus of RCF sandwich composite structures are lower than roof or floor rock single body and higher than coal single body when coal are taken different thicknesses. Main failure modes of coal and rock single bodies are cleavage, while main failure modes of RCF sandwich composite samples are shear. The peak strength and elastic modulus of RCF composite samples decrease with the increasing of coal thicknesses. The total input energy U, releasable elastic strain energy U e and dissipative energy U d all decrease first and then increase with increase of coal thickness. And a new damage constitutive model was established based on the dissipative energy and total input energy at peak strength, and damage evolution curve and equation of RCF composite samples were obtained. The study laid a foundation for the disaster evolution process of the RCF sandwich composite structures and mechanism of disaster time effect.